Dinasti Fatimiyah dan Implementasi Nilai ayat Al-Qur'an dalam Sistem Ekonomi Islam - Kotta, Iswan Kotta; Sefti Wahyuningsih; Alrasyid, Harun; Siradjuddin, Siradjuddin; Sudirman, Sudirman (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This article discusses Islamic economics during the Fatimid Dynasty. With the aim to find out how Islamic economics during the Fatimid Dynasty. This article uses literature- based qualitative research (library research) with a qualitative descriptive approach and technical descriptive analysis and content analysis. The results of this study show that Islamic economics during the Fatimid Dynasty progressed during the caliph al-Mu'izz, al- zAziz and al-Hakim. With several background factors such as the transfer of government centers from Tunisia to Cairo, extracting sources of economic income in all fields, integrated management of the fields of Agriculture, Trade and Industry, high exceptions to Science, harmonious relations with nonMuslims and tolerance which is very high for the community.